1991
DOI: 10.1111/j.1442-9993.1991.tb01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting patterns of post‐fire germination in 35 eastern Australian Fabaceae

Abstract: Germination in 35 speeies from 15 legume genera of southeastern Australia was promoted by a heat treatment which broke the seed coatcaused dormancy. Once the critical temperature was reached, most seeds had their dormancy broken, independent ofthe duration of heating. Speeies fell into three classes according to whether their dormanev was broken by a temperature of 40. 60 or 80°C.Highest germination in all speeies was achieved by heating in the temperature range 80-100°C. although long durations (120 min) at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
316
1
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 304 publications
(342 citation statements)
references
References 20 publications
22
316
1
3
Order By: Relevance
“…Several studies in agricultural systems found that the hard seeds of clover, Trifolium subterraneum, softened in response to daily temperature regimes between 30 and 60 C, if treated for several weeks or months (Hagon 1971;Taylor 1981). Auld and O'Connell (1991) observed that many leguminous species from south-eastern Australia had their physical dormancy broken to varying degrees by temperatures experienced during fire. The most important factor breaking dormancy was temperature, with a few species reaching significant germination levels after treatment at 40 and 60 C, but most reaching their maximum germination after treatment at 80À100 C. The duration of exposure did not significantly change the effect on dormancy, however, it should be noted that temperatures maintained in the soil during fire are short and exposure duration was tested over a scale of only minutes (Bradstock and Auld 1995).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies in agricultural systems found that the hard seeds of clover, Trifolium subterraneum, softened in response to daily temperature regimes between 30 and 60 C, if treated for several weeks or months (Hagon 1971;Taylor 1981). Auld and O'Connell (1991) observed that many leguminous species from south-eastern Australia had their physical dormancy broken to varying degrees by temperatures experienced during fire. The most important factor breaking dormancy was temperature, with a few species reaching significant germination levels after treatment at 40 and 60 C, but most reaching their maximum germination after treatment at 80À100 C. The duration of exposure did not significantly change the effect on dormancy, however, it should be noted that temperatures maintained in the soil during fire are short and exposure duration was tested over a scale of only minutes (Bradstock and Auld 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These species are characterised by having soil-stored seed banks and by having seeds with physical dormancy which is broken by heat (Auld and O'Connell 1991;Ooi 2007 The direct effects of fire in breaking physical dormancy of most of our study species have been previously studied in laboratory experiments by Auld and O'Connell (1991). The most important factor breaking dormancy was temperature, whereas the time of exposure had variable effects (1-120 min).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations